High-Performance AD and DA Converters, IC Design in Scaled Technologies, and Time-Domain Signal Processing Advances in Analog Circuit Design 2014 - Harpe, Pieter; Baschirotto, Andrea; Makinwa, Kofi A. A. (Springer International Publishing : Imprint: Springer, 2015)
This book is based on the 18 tutorials presented during the 23rd workshop on Advances in Analog Circuit Design.  Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, serving as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development.    • Includes coverage of high-performance analog-to-digital and digital to analog converters, integrated circuit design in scaled technologies, and time-domain signal processing; • Provides a state-of-the-art reference in analog circuit design, written by experts from industry and academia; • Presents material in a tutorial-based format.